2011
DOI: 10.1074/jbc.m110.192641
|View full text |Cite
|
Sign up to set email alerts
|

Angiopoietin-1/Tie2 Signal Augments Basal Notch Signal Controlling Vascular Quiescence by Inducing Delta-Like 4 Expression through AKT-mediated Activation of β-Catenin

Abstract: Angiopoietin-1 (Ang1) regulates both vascular quiescence and angiogenesis through the receptor tyrosine kinase Tie2. We and another group previously showed that Ang1 and Tie2 form distinct signaling complexes at cell-cell and cell-matrix contacts. We further demonstrated that the former up-regulates Notch ligand delta-like 4 (Dll4) only in the presence of cell-cell contacts. Because Dll4/Notch signal restricts sprouting angiogenesis and promotes vascular stabilization, we investigated the mechanism of how the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
88
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 105 publications
(95 citation statements)
references
References 52 publications
(65 reference statements)
5
88
2
Order By: Relevance
“…For example, pericyte marker expression in cells cultured from bone marrow increases with notch signalling (Stewart et al, 2011), and a recent study suggested that the stabilising effect of ANG1/TIE2 signalling between pericytes and ECs is mediated via induction of DLL4 expression in ECs (Fig. 5) (Zhang et al, 2011). However, the full relevance of these observations for pericyte-mediated stability in vivo remains unclear, as previous studies reported no defects in pericyte recruitment in DLL4-deficient mice.…”
Section: Network Formation: Remodelling and Maturationcontrasting
confidence: 42%
See 1 more Smart Citation
“…For example, pericyte marker expression in cells cultured from bone marrow increases with notch signalling (Stewart et al, 2011), and a recent study suggested that the stabilising effect of ANG1/TIE2 signalling between pericytes and ECs is mediated via induction of DLL4 expression in ECs (Fig. 5) (Zhang et al, 2011). However, the full relevance of these observations for pericyte-mediated stability in vivo remains unclear, as previous studies reported no defects in pericyte recruitment in DLL4-deficient mice.…”
Section: Network Formation: Remodelling and Maturationcontrasting
confidence: 42%
“…The activation of DLL4/notch signalling in ECs has a vessel stabilising effect via inhibition of angiogenic sprouting (Hellstrom et al, 2007;Leslie et al, 2007;Lobov et al, 2007;Siekmann and Lawson, 2007;Suchting et al, 2007). Notch signalling also promotes vascular stabilisation more directly through the induction of notchregulated ankyrin repeat protein (NRARP) expression (Phng et al, 2009) and via the production of ECM components (Benedito et al, 2008;Trindade et al, 2008;Zhang et al, 2011). NRARP limits notch signalling and promotes WNT/CTNNB1 signalling in stalk cells, which supports vascular stability and prevents EC retraction by inducing proliferation and improving intercellular junctions (Fig.…”
Section: Network Formation: Remodelling and Maturationmentioning
confidence: 99%
“…Notch and VEGF pathway interactions have been thoroughly studied in retinal sprouting angiogenesis, but only 1 study thus far has analyzed the Dll4/Notch crosstalk with angiopoietin/ Tie2 signaling (53). We showed here that Dll4/Notch signals were tumor cell survival.…”
Section: Discussionmentioning
confidence: 64%
“…Notch-regulated ankyrin repeat protein acts as a molecular link between the Notch and Wnt/β-catenin pathways in ECs (Phng et al, 2009). Furthermore, the Wnt/β-catenin pathway potentiates Notch signaling by inducing the expression of Dll4, which modulates vascular remodeling and arterial EC specification during early development (Corada et al, 2010;Yamamizu et al, 2010;Zhang et al, 2011). However, a recent report indicated that Dll4 expression in ECs and subsequent arterial specification are not mediated by the Wnt/β-catenin pathway in vivo (Wythe et al, 2013).…”
Section: Introductionmentioning
confidence: 98%